Feasibility Study of Grid-Connected Solar Photovoltaic (PV) System for Primary School in Johor - Siti Amely Jumaat; Adhwa Amsyar Syazwan Ab Majid; Chin Kim Gan; Mohd Noor Abdullah; Nur Hanis Radzi; Rohaiza Hamdan; Suriana Salimin (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
This project aims to determine the potential of grid connected solar Photovoltaic (PV) implementation and project planning of solar PV System in school.  Generally, the educational institution used huge amount of electricity to operate so their monthly bills is expensive. Therefore, the project planning is necessary to determine the potential of solar PV system implementation. The project planning consists of the current electricity consumed by the school and the amount of 120W Monocrystalline PV module needed by them. The cost of project are determines to identify the initial cost of this project implementation. Lastly, analysis on the profit collected by SK Pintas Raya after 20 years of solar PV system implementation proved the importance of this project.